2003
DOI: 10.1046/j.1440-1746.2003.02852.x
|View full text |Cite
|
Sign up to set email alerts
|

Liver cirrhosis developed after ketoconazole‐induced acute hepatic injury

Abstract: We describe a previously healthy woman who developed liver cirrhosis as a sequela of acute hepatic injury that was induced by ketoconazole administration to treat onychomycosis. The initial presentation of the disease was of a typical acute hepatitis, characterized by nausea, anorexia, fatigue, and jaundice that developed during the administration of ketoconazole. Many other causes of hepatitis were absent in the patient. Even though the hepatic injury was gradually resolved for several months after cessation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
8
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…The observed histopathological alterations ranged from moderate to severe changes according to the dose used and to the length of the period of administration. The findings of many human and animal studies using several antifungal drugs were consistent with the present results (Adriaenssens et al., ; Liu et al., ; Chien et al., ; Kim et al., ). Histopathological changes such as inflammation and fibrosis were also observed in the liver of rats that received repeated doses of itraconazole (Norshahida, ).…”
Section: Discussionsupporting
confidence: 92%
“…The observed histopathological alterations ranged from moderate to severe changes according to the dose used and to the length of the period of administration. The findings of many human and animal studies using several antifungal drugs were consistent with the present results (Adriaenssens et al., ; Liu et al., ; Chien et al., ; Kim et al., ). Histopathological changes such as inflammation and fibrosis were also observed in the liver of rats that received repeated doses of itraconazole (Norshahida, ).…”
Section: Discussionsupporting
confidence: 92%
“…In addition, investigators want to minimize exposure of healthy volunteers to KTZ because it may cause liver damage. 5,6 Although SD KTZ may be acceptable in some inhibition studies, the pharmacokinetic characteristics of the CYP3A substrate to be evaluated may influence the extent of inhibition by SD KTZ. For example, a study that evaluates a CYP3A substrate with a t 1/2 much longer than that of KTZ may require that additional MD KTZ be given following substrate administration.…”
mentioning
confidence: 99%
“…Some studies have reported clinical adverse effects after therapy with various systemic anti-fungal agents (Kim et al 2003;Figg et al 2010). Several case reports of mild-to-severe hepatic injury, including icteric and fatal cases, have been published (Kim et al 2003;Figg et al 2010). For instance, the adverse effects of griseofulvin include gastrointestinal symptoms, allergic reactions, photodermatitis, hepatic and renal dysfunctions.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, one month after the last treatment with enilconazole, all animals were cured as assessed by clinical and mycological evaluation (Schepens and Spanoghe 1981). Some researchers reported that several systemic antifungal agents have adverse effects resulting in mild-tosevere hepatic injuries and renal syndromes in cats (Kim et al 2003;Figg et al 2010). Enilconazole is generally well tolerated but has also been associated with hypersalivation, anorexia, weight loss, emesis, idiopathic muscle weakness, and slightly elevated serum alanine aminotransferase (ALT) concentrations (Dejaham 1998;Hnilica and Medleau 2002 Nigella sativa (NS), an annual herbaceous plant of the Ranunculaceae, has been used traditionally in the Middle East, Northern Africa, Far East and Asia for the treatment of various diseases for over 2000 years (Phillips 1992).…”
mentioning
confidence: 99%